Differences in effectiveness of water steeping from green tea leaf and black tea leaf as hemostasis effect on wound cut-tail mice (mus musculus) - Hasmawati Hasan; Wenni Raharja (Journal of Dentomaxillofacial Science, 2016)
Tooth extraction is a simple procedure that is frequently performed in the practice of dentistry. Bleeding is a common complications of tooth extraction. There are several materials or methods that may be used to control the bleeding. To minimize side effect, it might need natural ingredients as a replacement. Tannin and flavonoid is a compounds that can reduce bleeding time. Green tea and black tea are plants that have these compounds with different concentrations. Aims of this study is to determine the differences in the effectiveness of water steeping green tea leaves and black tea leaves as a hemostasis effect on wound cut-tail mice (Mus musculus). This is an experimental research with study design post-test only control group design. Samples were 30 male mice which divided into three groups. One negative control group (aquadest) and two treatment group (green tea and black tea). Mice that match the criteria is cutted the tail equal to 3 mm from the tip of the tail, then the ingredients is applied to the wound. Blood is dripped on absorbent paper until bleeding stop and data were analyzed using Kruskal-Wallis. There are significant differences between negative control group and the treatment group. In the treatment groups there were significant differences in the bleeding time between green tea group and black tea group. As a conclusion, water steeping from green tea leaves have a better effect than black leaves tea as hemostasis on wound cut-tail mice.